2014
DOI: 10.5455/jice.20140523104104
|View full text |Cite
|
Sign up to set email alerts
|

Antigiardial effect of <i>Anethum graveolens </i>aqueous extract in children

Abstract: Background:Giardia lamblia is the most common intestinal parasite of humans identified worldwide. In spite of metronidazole (Met) is the most commonly used drug for the treatment of giardiasis in humans, low patient compliance and side-effects, especially in children encourage efforts to look for new and safe agent; many plants used in folk medicine thought to have antigiardial effect, Anethum graveolens (AG) (dill) is an annual herb cultivated in Iraq used both as a medicinal agent and as food spice. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…The study revealed that 5 days’ consummation of the extract and the regular dose of metronidazole improved symptoms earlier than treatment with metronidazole alone. 69 The second study evaluated the protective effects of dill extracts on amoebic liver abscess through in vivo and in vitro studies at multiple concentrations. The study revealed very promising anti-protozoal effects in comparison to metronidazole effects.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that 5 days’ consummation of the extract and the regular dose of metronidazole improved symptoms earlier than treatment with metronidazole alone. 69 The second study evaluated the protective effects of dill extracts on amoebic liver abscess through in vivo and in vitro studies at multiple concentrations. The study revealed very promising anti-protozoal effects in comparison to metronidazole effects.…”
Section: Discussionmentioning
confidence: 99%
“… Anethum graveolens Apiaceae Leave Aqueous extract Iraq 1 ml 3 times a day for 5 days Trophozoite-cysts This study showed that pediatric patients with giardiasis may benefit from 5 days treatment with AGAE administered as 1 ml 3 times daily, the improvement in the symptom with this herbal agent was comparable to the standard pharmacological agent Met; results showed that AG is safe and tolerable over treatment course. 2014 ( Sahib et al, 2014 ) Mentha crispa Lamiaceae Leave Aqueous extract Brazil 2 g/day for 10 days Cyst Results showed that the cure rate for the Secnidazole group (84.0%) was significantly higher (P = 0.0002) as that verified in the M. crispa group (47.83%). 2011 ( Teles et al, 2011 ) Triticum Vulgare (Wheat) Poaceae Germ Oil Canada 2 g, 3 times a day for 7 days Cyst In asymptomatic and symptomatic subjects, both cyst passage and coproantigen levels were significantly reduced in those taking WG compared with the placebo group (P < 0.01 and P = 0.06, respectively).…”
Section: Resultsmentioning
confidence: 93%
“…Infants younger than 1 year infected by Giardia lamblia, which induces a massive diarrhea, were orally dosed with a water extract of dill leaves (3 times/d) for 5 days. 54 Compared with baseline values, for those given dill extract, the prevalence of Giardia trophozoites or cysts in stools and the frequency of bowel movements Abbreviations: APGAR, score for standard assessment of infant health after delivery (Appearance, Pulse, Grimace, Activity, and Respiration); bw, body weight; C-section, cesarean delivery procedure; F/R ratio, duration of time for a contraction to return to baseline from its peak (fall) divided by the duration of its rise time to its peak (rise); GI, gastrointestinal; HR, heart rate; IV, intravenous; NE, no statistically significant effect. symptoms of infection, which were similar to the outcomes for subjects administered the antifungal agent clotrimazole.…”
Section: Other Miscellaneous Effectsmentioning
confidence: 99%